Antioxidant and Anthocyanin-Rich Vinegar Fermented from Thai Colored Rice Varieties - Saithong, Pramuan; Permpool, Jirawut; Nitipan, Supachai (Trends in Sciences, 2024)
This study aims to produce antioxidant and anthocyanin-rich vinegar using three types of Thai rice through surface culture fermentation (SCF). Three varieties of Thai rice with different colors, including Khao Dawk Mali 105 (white color), Sangyod (brown color) and Hom Nil (black color), were used as a substrate for vinegar fermentation. The different Thai rice varieties were hydrolyzed by boiling and enzymatic hydrolysis. The sweetness of the hydrolyzates was adjusted by adding granulated sugar at 20 °Brix and using it as a substrate. A mixed culture of Saccharomyces cerevisiae var. burgundy and S. cerevisiae var. kyokai was used as a yeast starter for alcohol fermentation. After 4 weeks of fermentation, Acetobacter aceti TISTR 354 required only 10 days to convert alcohol into acetic acid by the surface-culture fermentation method. Vinegar produced from the Thai rice varieties contained acetic acid at a concentration of more than 4.0 % (v/v), with residual alcohol concentrations less than 0.5 % (v/v). Hom Nil vinegar presented an anthocyanin content of 2.39 ± 0.44 mg/L and had the highest antioxidant activity, with 428.47 ± 4.04 g/mL (Total phenolic content; TPC), 71.80 ± 0.00 g/mL (Ferric reducing antioxidant power assay; FRAP), and 49.27 ± 0.27 % inactivation (2,2-Diphenyl-1-picrylhydrazyl; DPPH). A sensory panel rated the vinegar fermented from the three varieties as ‘like slightly’ on a 9-point hedonic scale. HIGHLIGHTS Three distinct Thai rice varieties, each with unique colors (white, brown, and black), were utilized as substrates for vinegar fermentation Hydrolysis of the rice substrates involved boiling and enzymatic processes, with sweetness adjusted using granulated sugar at 20 °Brix A mixed culture of cerevisiae var. burgundy and S. cerevisiae var. kyokai served as a yeast starter for alcohol fermentation The innovative surface-culture fermentation method employed Acetobacter aceti TISTR 354, converting alcohol into acetic acid in just 10 days Hom Nil rice vinegar exhibited remarkable attributes, with an anthocyanin content of 2.39 ± 0.44 mg/L and exceptional antioxidant activity (428.47 ± 4.04 g/mL TPC, 71.80 ± 0.00 g/mL FRAP and 49.27 ± 0.27 % DPPH inactivation) Sensory evaluation by a panel yielded a ‘like slightly’ rating on a 9-point hedonic scale for vinegars derived from all 3 rice varieties GRAPHICAL ABSTRACT